SOCIAL ENTREPRENEURSHIP: INNOVATION, DEVELOPMENT, SOLUTIONS - DAVYDKOVA, KATERYNA; OBEREMCHUK, VALENTYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The dynamic present in Ukraine forms a new interpretation of the concept of "entrepreneurship". In the modern sense, entrepreneurship involves identifying, evaluating and using new, as yet unseen opportunities to attract the attention of consumers and maximize profits. In this sense, opportunities are a tool for finding innovation and creating new products or services. According to the Business Dictionary, entrepreneurship means the ability and desire to organize a business, taking into account the potential risks, in order to profit from it. According to Lowry, the concept of "entrepreneur" is defined as a person who seeks to achieve their goals in the economic space, to meet their desires and needs. According to the position of the consulting company McKenzie, entrepreneurs are responsible for improving the lifestyle of consumers, as well as for solving the problems faced by consumers. Most of these problems are social in nature. An enterprise that seeks tools of influence to solve such problems is called social. In our opinion, social entrepreneurship is a field of activity that can have both commercial and non-commercial basis, all efforts of which are aimed not at maximizing profits, but at solving social problems with innovative ideas. The spread of social entrepreneurship is currently fragmented and in its infancy. Entrepreneurs who choose to engage in social enterprises are often called innovators because they try to solve "outdated" social problems with "new" entrepreneurial approaches. Most researchers confirm the view that social entrepreneurship is entrepreneurship with innovation and even social entrepreneurship itself is called innovation in the social sphere. The definitions of social entrepreneurship are considered in the work, its innovative content is determined. Innovative social entrepreneurship in Ukraine is analyzed. The effectiveness of the introduction of social enterprises to solve social problems is substantiated. Examples of functioning social enterprises in Ukraine are given and social enterprises that are currently represented in Ukraine are grouped into three groups. The main stages of implementation of social entrepreneurship are summarized.